Macrophage Activation Syndrome in a Child Affected by Malaria: The Choice of Steroid. (April 2013) - Trapani, S.; Canessa, C.; Fedi, A.; Giusti, G.; Barni, S.; Montagnani, C.; Galli, L.; Resti, M.; De Martino, M.
Macrophage activation syndrome is a potentially fatal clinical syndrome caused by an excessive activation and proliferation of macrophages and T cells, leading to an exaggerated inflammatory reaction. It is well known that it can complicate the course of different conditions, especially autoimmune, lympho-proliferative, infectious diseases and drugs. Many infective pathogens can trigger the syndrome but the association with malaria has rarely been described, especially in children. We report a child with severe malaria complicated by MAS, in whom the clinical appearance of this syndrome could be considered as worsening of malaria itself. Furthermore, the use of steroids as first choice drugs in this complication, but arguable in malaria, has been highlighted. Clinicians should be aware of this syndrome when malaria does not respond to conventional therapy, since early diagnosis and prompt treatment may dramatically reduce the mortality associated with this condition.